Letters in the forest: global precedence effect disappears for letters but not for non-letters under reading-like conditions - Lachmann, Thomas; Schmitt, Andreas; Braet, Wouter; van Leeuwen, Cees (Frontiers in Psychology, 2014)
Normally-skilled reading involves special processing strategies for letters, which are habitually funneled into an abstract letter code. On the basis of previous studies we argue that this habit leads to the preferred usage of an analytic strategy for the processing of letters, while non-letters are preferably processed via a holistic strategy. The well-known Global Precedence Effect (GPE) seems to contradict to this assumption, since, with compound, hierarchical figures, including letter items, faster responses are observed to the global than to the local level of the figure, as well as an asymmetric interference effect from global to local level. We argue that with letters these effects depend on presentation conditions; only when they elicit the processing strategies automatized for reading, an analytic strategy for letters in contrast to non-letters is to be expected. We compared the GPE for letters and non-letters in central viewing, with the global stimulus size close to the functional visual field in whole word reading (6.5o of visual angle) and local stimuli close to the critical size for fluent reading of individual letters (.5o of visual angle). Under these conditions, the GPE remained robust for non-letters. For letters, however, it disappeared: letters showed no overall response time advantage for the global level and symmetric congruence effects (local-to-global as well as global-to local interference). We interpret these results as according to the view that reading is based on resident analytic visual processing strategies for letters.